2017
DOI: 10.4103/0300-1652.218411
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular function in patients with heart failure in a cardiac clinic in Southwest Nigeria

Abstract: Background:Right ventricular (RV) function is an important entity in heart failure. Patients with RV dysfunction (RVD) have poorer prognosis and exercise tolerance than those with preserved RV systolic function. Tricuspid annular plane systolic excursion (TAPSE) has been proposed as a simple and reproducible parameter for the qualitative assessment of RV systolic function/ejection fraction (EF). This study aims at describing RV function/RVD among heart failure patients in a specialized cardiac facility in Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Most of the reported studies, however, had been used in assessing right ventricular function in adult patients with heart failure. 18 In our study, we found that fTAPSE values increase linearly with gestational age and foetal weight. Hence, considering ongoing developmental changes it was deemed more useful to have a reference ranges of fTAPSE for both gestational age and foetal weight rather than a single value, as seen in Tables 4 and 5 respectively.…”
Section: Correlation Between Gestational Age Estimated Foetal Weight ...supporting
confidence: 55%
“…Most of the reported studies, however, had been used in assessing right ventricular function in adult patients with heart failure. 18 In our study, we found that fTAPSE values increase linearly with gestational age and foetal weight. Hence, considering ongoing developmental changes it was deemed more useful to have a reference ranges of fTAPSE for both gestational age and foetal weight rather than a single value, as seen in Tables 4 and 5 respectively.…”
Section: Correlation Between Gestational Age Estimated Foetal Weight ...supporting
confidence: 55%
“…In addition, this study also demonstrated that the left atrial function index had no correlation with tricuspid annular plane systolic excursion, and this may be due to the fact that the population of this study was mostly patients with chronic stable heart failure who were routinely followed up in the clinic. A study from Nigeria [ 22 ] reported a similar finding, but it is different from another work from the same country [ 23 ] that studied the right ventricular function in patients with heart failure in a cardiac clinic and demonstrated that left atrial diameter correlated negatively with tricuspid annular plane systolic excursion.…”
Section: Discussionmentioning
confidence: 75%
“…This radiological feature of the foetal left ventricular function in normal pregnancy has not yet been extensively investigated, especially in Nigeria. The majority of the reported investigations had focused on evaluating right and left ventricular performance in adults with heart conditions [17][18][19][20][21] . A few other authors compared cardiac function between foetuses of women with diabetes mellitus in pregnancy and those with normal pregnancies [1,8] .…”
Section: Discussionmentioning
confidence: 99%